PENERAPAN TEKNOLOGI TEPAT GUNA PENGRAJIN TEMPE DUSUN LATSARI UNTUK MENINGKATKAN PRODUKTIVITAS - Wulandari, Lusi Mei Cahya; Patrick, Johan; Yoseph, Deograsias; Sumewang, Filippo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2023)
In facing tough competition, tempe small and medium enterprises (SMEs) need to pay attention to the arrangement of their production facilities. A well-organized and tidy production facility helps improve production process efficiency. This has an impact on the quality of tempe, ensuring it meets the established standards. Desa Mlirip in Jetis sub-district, Mojokerto, has seven Tempe Home Industries (IRT) with the largest production located in Dusun Latsari, owned by Mr. Riono, with a minimum daily production of 600 kg. The issue faced by the partners is that the soybean washing process is done manually, which leads to employee fatigue and a lack of hygiene. The goal of this Community Partnership Program is to increase the productivity of tempe producers through the creation of a soybean washing machine, resulting in a faster production process and better product quality. The steps taken include designing a 100kg capacity washing machine, manufacturing the machine, conducting trials, and implementing the machine on the production floor. The results of implementing the soybean washing machine have led to a 27.70% cost savings and have lightened the workload for operators at the tempe business in Dusun Latsari. Keywords: Tempeh, Soybean Washing Machine; Productivity